ANXA2 is a potential biomarker for cancer prognosis and immune infiltration: A systematic pan-cancer analysis - Ning, Yijie; Li, Yufei; Wang, Hongqin (Frontiers in Genetics, 2023)
Background: Annexin A2 (ANXA2) belongs to the Annexin A family and plays a role in epithelial-mesenchymal transition, fibrinolysis, and other physiological processes. ANXA2 has been extensively implicated in tumorigenesis and development in previous studies, but its precise role in pan-cancer remains largely unknown. Methods: We adopted bioinformatics methods to explore the oncogenic role of ANXA2 using different databases, including the Cancer Genome Atlas (TCGA), the Genotype-Tissue Expression (GTEx) biobank, the Human Protein Atlas (HPA), the Gene Expression Profiling Interaction Analysis (GEPIA) and cBioPortal. We analyzed the differential expression of ANXA2 in different tumors and its relationship with cancer prognosis, immune cell infiltration, DNA methylation, tumor mutation burden (TMB), microsatellite instability (MSI) and mismatch repair (MMR). Furtherly, we conducted a Gene Set Enrichment Analysis (GSEA) to identify the ANXA2-related pathways. Results: ANXA2 expression was upregulated in most cancers, except in kidney chromophobe (KICH) and prostate adenocarcinoma (PRAD). ANXA2 showed a good diagnostic efficacy in twelve types of cancer. The high expression of ANXA2 was significantly associated with a reduced overall survival, disease-specific survival and progression-free interval in seven cancers. The ANXA2 expression was variably associated with infiltration of 24 types of immune cells in 32 tumor microenvironments. In addition, ANXA2 expression was differently associated with 47 immune checkpoints, immunoregulators, DNA methylation, TMB, MSI and MMR in pan-cancer. GSEA revealed that ANXA2 was significantly correlated with immune-related pathways in fifteen cancers. Conclusion: ANXA2 widely correlates with immune infiltration and may function as a promising prognostic biomarker in many tumors, showing its potential as a target for immunotherapy in pan-cancer.